2020
DOI: 10.1177/2042098620957142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stratified medication review in high-risk patients at admission to hospital: a randomised controlled trial

Abstract: Background: Patients at high risk of medication errors will potentially benefit most from medication reviews. An algorithm, MERIS, can identify the patients who are at highest risk of medication errors. The aim of this study was to examine the effects of performing stratified medication reviews on patients who according to MERIS were at highest risk of medication errors. Methods: A randomised controlled trial was performed at the Acute Admissions Unit, Aarhus University Hospital, Denmark. Patients were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 31 publications
0
25
0
6
Order By: Relevance
“…Procedures for medication review have been implemented in many countries to improve rational medication use 58 . Number of prescribed medications is often used as a selection criteria for medication reviews, 59 and many strategies, screening tools and prescribing algorithms have been developed to prevent inappropriate prescribing and optimize medication use in the ED 32–35,60–62 . A recent systematic review identified 42 potential tools for assessing appropriateness of prescribed medications 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Procedures for medication review have been implemented in many countries to improve rational medication use 58 . Number of prescribed medications is often used as a selection criteria for medication reviews, 59 and many strategies, screening tools and prescribing algorithms have been developed to prevent inappropriate prescribing and optimize medication use in the ED 32–35,60–62 . A recent systematic review identified 42 potential tools for assessing appropriateness of prescribed medications 26 .…”
Section: Discussionmentioning
confidence: 99%
“…58 Number of prescribed medications is often used as a selection criteria for medication reviews, 59 and many strategies, screening tools and prescribing algorithms have been developed to prevent inappropriate prescribing and optimize medication use in the ED. [32][33][34][35][60][61][62] A recent systematic review identified 42 potential tools for assessing appropriateness of prescribed medications. 26 However, disease burden was not included as a tool in this study.…”
Section: Stratification Of Medication Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent randomized controlled trial, including 375 patients with similar mean age and number of drugs as our population, used the MERIS to perform stratified CMRs in patients at the highest risk of DRPs. 39 The trial was conducted at an acute admissions unit, where intervention patients with a MERIS score ≥14 received a CMR by either a clinical pharmacist (score 14 to 26) or a clinical pharmacologist (score ≥26). In total, 34% of the patients in the intervention group were identified as high-risk patients according to the MERIS.…”
Section: Medication Risk Score Performance Across Populationsmentioning
confidence: 99%